Developing Reading Tasks for Autonomous Learning for Grade X Students of SMA 1 Sleman - Sungkawati Kardi Wahyuningsih; Joko Priyana (LPPM UNY, 2013)
This research study was aimed at developing reading tasks for autonomous learning for grade X students of Senior High School 1 Sleman to help the students improve their reading skills independently. This research was a Research and Development study that included the steps of needs analysis, course grid design, product development, product validation, product revision, try-out, and study of the final product. This research developed five units of reading tasks for autonomous learning. The reading tasks were developed according to the needs analysis data. The need of grade X students of Senior High School 1 Sleman in learning reading autonomously is to improve their reading skills. the appropriate reading tasks for autonomous learning are that they give clear instructions, describe the language skills clearly, look nice, give a lot practice, give feedback and give answers or let the learners know how to complete the tasks, give examples and tell the learners how to learn best. The needs related appropriate reading tasks for autonomous learning in terms of their components that are: the goal of learning reading autonomously is to improve the students' reading skills; the input presents interesting pictures; the procedure presents interesting and enjoyable activities; the learners' role is as the active reader; the teacher's role is the feedback giver; and the setting is individual work. The components of appropriate reading tasks for autonomous learning in terms of their organisations are arranged into four stages, namely introduction, activities, self-assessment, and check your achievement.